Research on Crystal Structure and Fungicidal Activity of the Amide Derivatives Based on the Natural Products Sinapic Acid and Mycophenolic Acid - Zhanfang Chen; Hongbin Fang; Xuewen Hua; Wenrui Liu; Yi Liu; Chenmeng Xue; Bingxiang Wang; Dzmitry Bazhanau; Xiaohe Zhu; Man Yuan; Jing Ru; Pengfei Chu (Journal of Chemistry)
Structural optimization based on natural products is an important and effective way to discover new green pesticides. Here, two series of amide derivatives based on sinapic acid and mycophenolic acid were designed in combination with the fungicidal natural product piperlongumine and synthesized by preparing the carboxylic acid into acyl chloride and then reacting with the corresponding aromatic amines, respectively. The resulting structures were successively characterized by 1H NMR, 13 C NMR, and HRMS. The crystal structures of molecules I-4 and II-5 were analyzed for structure validation. The in vitro inhibitory activity indicated that most of the target products exhibited fungicidal activity equivalent to or even better than fluopyram against Physalospora piricola. The in vivo fungicidal activity demonstrated that the compounds I-5 and II-4 displayed almost the same preventative activity as carbendazim and fluopyram at 200 μg mL−1. The TEM observation revealed that the fungicidal activity of the target molecules against Physalospora piricola may be due to the influence on the mitochondria in the cell structure. These results will provide valuable theoretical guidance for developing the new green fungicides.